Symmetrization of a heat conduction model for a rigid medium (Archives of Mechanics - Test, 1996)
The symmetrization of the equations of a heat conduction model for a rigid medium in time and three space dimensions is performed. The general symmetrizability condition is formulated in terms of the entropy function. Examples of particular models (e.g. Debye's model) are discussed.